Analisis Faktor Internal Dan Faktor Eksternal Yang Mempengaruhi Preferensi Pedagang Pasar Godean Terhadap Para Rentenir - Rika May Linda Anggraini; Akhmad Arif Rifan (Islamic Economics, Finance, and Banking Review, 2024)
The present study aims to determine the internal and external factors affecting the loan shark preference of the Godean Market merchants in carrying out business financing and to analyze the most dominant factor affecting the loan shark preference of the Godean Market merchants in carrying out business financing. The research type was qualitative descriptive phenomenological. The present study used primary and secondary data. The present study used a non-probability sampling technique. The informants in the present study were the management and merchants at GodeanMarket. Based on the research result, the number of traders is greater than that of loan sharks who control Godean Market, loan sharks from institutions, and individuals from Yogyakarta and Sumatra. It is concluded that the internal factors affecting the loan shark preference of Godean market merchants are declining income, a convenient loan system, and a manageable installment system based on their ability to carry out their obligations. Meanwhile, the external factors affecting the loan shark preference of Godean market merchants are market relocation, minimum risk, and lack of access to formal financial institutions. The dominant factors are declining income, convenient loan or financing systems, and installment systems.